Ancient Seafarer and Maritime Early Civilization in Southeast Asia: Theoretical Debate and New Approach - Ismail Ali (International Journal of Business and Social Science Research, 2024)
Traditionally, seas and oceans have become sources of inspiration in seeking the truth from facts to dispel the worldview of those who tended to associate it with myths and superstitions. Seas and oceans are equally realms with their advantages in bridging nations, inculcating a sense of unity, mutual understanding, and cooperation as well as in generating wealth. They are considered priceless treasures, which can neither be exchanged nor modified. In the South East Asia or Nusantara historiography, the relationship between men known as seafarers is indisputable. It is not far-fetched to suggest that the change and development in present-day Southeast Asia, from traditional kingdoms to modern nation-states are intimately rooted in and shaped by the contributions of our seafaring ancestors. By taking into consideration past maritime historiography, namely the roles and contributions of these seafaring communities, and the presence of the surrounding seas and oceans, it can be deduced that they have contributed immensely to the development of various civilizations in this region.